Etnografija medgeneracijskih odnosov Dom in delo na kmetijah skozi življenjske pripovedi - Knežević Hočevar, Duška (ZRC SAZU, Založba ZRC, 2013)
In the monograph ('Ethnography of intergenerational relations: home and work on farms through life stories'), intergenerational relationships are discussed along the lines of demographical anthropology (Chapter 1).